Single cell analysis of docosahexaenoic acid suppression of sequential LPS-induced proinflammatory and interferon-regulated gene expression in the macrophage - Wierenga, Kathryn A.; Riemers, Frank M.; Westendorp, Bart; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2022)
Preclinical and clinical studies suggest that consumption of long chain omega-3 polyunsaturated fatty acids (PUFAs) reduces severity of chronic inflammatory and autoimmune diseases. While these ameliorative effects are conventionally associated with downregulated expression of proinflammatory cytokine and chemokine genes, our laboratory has recently identified Type 1 interferon (IFN1)-regulated gene expression to be another key target of omega-3 PUFAs. Here we used single cell RNA sequencing (scRNAseq) to gain new mechanistic perspectives on how the omega-3 PUFA docosahexaenoic acid (DHA) influences TLR4-driven proinflammatory and IFN1-regulated gene expression in a novel self-renewing murine fetal liver-derived macrophage (FLM) model. FLMs were cultured with 25 µM DHA or vehicle for 24 h, treated with modest concentration of LPS (20 ng/ml) for 1 and 4 h, and then subjected to scRNAseq using the 10X Chromium System. At 0 h (i.e., in the absence of LPS), DHA increased expression of genes associated with the NRF2 antioxidant response (Sqstm1, Hmox1, Chchd10) and metal homeostasis (Mt1, Mt2, Ftl1, Fth1), both of which are consistent with macrophage polarization to a more anti-inflammatory phenotype. At 1 h post-treatment, DHA inhibited LPS-induced cholesterol synthesis genes (Scd1, Scd2, Pmvk, Cyp51, Hmgcs1, and Fdps) which potentially could contribute to interference with TLR4-mediated inflammatory signaling. At 4 h post-treatment, LPS-treated FLMs reflected a more robust inflammatory response including upregulation of proinflammatory cytokine (Il1a, Il1b, Tnf) and chemokine (Ccl2, Ccl3, Ccl4, Ccl7) genes as well as IFN1-regulated (Irf7, Mx1, Oasl1, Ifit1) genes, many of which were suppressed by DHA. Using SCENIC analysis to identify gene expression networks, we found DHA modestly downregulated LPS-induced expression of NF-κB-target genes. Importantly, LPS induced a subset of FLMs simultaneously expressing NF-κB- and IRF7/STAT1/STAT2-target genes that were conspicuously absent in DHA-pretreated FLMs. Thus, DHA more potently targeted the IFN1 response than the NF-kappaB response. Altogether, scRNAseq generated a valuable dataset that provides new insights into multiple overlapping mechanisms by which DHA may transcriptionally or post-transcriptionally regulate LPS-induced proinflammatory and IFN1-driven responses in macrophages.